Optimization of Hydrothermal Carbonization Time of Dimocarpus longan Peel: Adsorption Selectivity and Regeneration Performance for Dyes - Wijaya, Alfan; Ahmad, Nur; Utami, Hasja Paluta (Indonesian Journal of Material Research, 2025)
This study investigates the hydrothermal carbonization (HTC) process of Dimocarpus longan peel for the development of a selective and regenerable adsorbent for cationic dye removal. The hydrochar was synthesized at 190°C with varying carbonization durations (4–12 hours) and characterized using XRD and FTIR analysis. XRD analysis revealed the formation of an amorphous carbon phase, particularly at longer HTC durations, with the most optimized structure observed at 10 hours. FTIR spectra confirmed that hydrothermal carbonization preserved the primary functional groups while modifying their intensity. Adsorption experiments using a binary dye system (malachite green-MG and rhodamine B-RhB) demonstrated that the hydrochar exhibited higher selectivity for MG, achieving a removal efficiency of 81.78%, compared to 41.88% for RhB. Desorption studies indicated that ethanol and acetone were the most effective desorbing agents, with desorption efficiencies of 18.99% and 18.14%, respectively, while water and acidic conditions showed minimal dye release. Regeneration tests revealed a gradual decline in adsorption capacity over three cycles, with removal efficiencies decreasing from 73.23% to 42.17%, indicating partial loss of adsorption sites and possible structural degradation. These findings suggest that Dimocarpus longan peel-derived hydrochar, particularly at 10-hour HTC processing, is a promising adsorbent for selective cationic dye removal. However, further optimization of regeneration techniques is necessary to improve its reusability and long-term performance.